THE CONTENT OF THEIR ACTIVITIES ACCORDING TO THE PSYCHODIAGNOSTIC NATURE OF THE AMTXAUER INTELLIGENCE TEST, WHICH IS PART OF THE INTELLIGENCE TESTS - Narkulov , Xusan Ismoilovich (Educational Research in Universal Sciences, 2024)
In Uzbekistan. M.Davletshin, E.Goziev, B.R.Kadyrov, M.Vohidov, V.M.Karimova, Z.T.Nishanova, K.B.Kadyrov, E.Z.Usmanova, T.S.Jo ‘ ryev, J.X.Mavlonov, Sh.R.Samarov, A.F.Azimovas and others conducted their scientific research on the issues of mental ability, interest, motive, talent, talent. The availability of the ability to qualify students with a high level of intelligence and intelligence in studies using intellectual tests and other psychodiagnostic techniques can conveniently and easily master the knowledge, skills and competencies given to these qualified students and successfully apply the acquired skills in practice.